The Influence of Financial Literacy and Financial Attitudes on The Financial Management Behavior of Bandar Lampung University Students: (Faculty Case Study Economics and Business Class of 2020) - Wijaya, Nicolas Dwi; Habibburrahman, Habibburrahman (LPPPIPublishing, 2023)
Students and female students must understand finance to perform well in financial management behavior. So that students can manage the income and expenditure of money well and can save or invest in the future. Financial literacy and financial attitudes can affect a person's financial management behavior. This study aims to know the relationship between financial literacy and financial attitudes toward financial management behavior of Bandar Lampung University students and students. The sample in this study amounted to 48 college students and female students. The data analysis method in this study used multiple linear regression and descriptive statistics. The results of this research conclude that the financial management behavior of students and female students is not effect by financial literacy, on the contrary financial management behavior is effect by their financial attitudes.